Desalted duck egg white peptides-chitosan oligosaccharide copolymers as calcium delivery systems: Preparation, characterization and calcium release evaluation in vitro and vivo. (May 2020) - Zhao, Mengge; Ma, Aimin; He, Hui; Guo, Danjun; Hou, Tao
Graphical abstract: Calcium delivery systems are highlighted to enhance Ca absorption through the two chemical mechanisms: Amadori-type linkage and transglutaminase (TGase) induced reaction. Highlights: Maillard and TGase reactions were used to prepare calcium nano-carriers. Two calcium nano-carriers restrained Ca 2+ release in stomach. Nano-carriers promoted calcium uptake in phytic acid-induced calcium deficiency mice model. Calcium nano-carriers could regulate gut microbiota and protect gut health. Abstract: Two novel calcium delivery systems with high calcium-binding ability were prepared with desalted duck egg white peptides (DPs) and chitosan oligosaccharide (COS) by Amadori-type linkage and transglutaminase (TGase) induced reaction. Fourier transform infrared spectroscopy (FTIR), Zeta potential and particle size analyses were used to characterize the copolymers. These two copolymers reversed the inhibition of phytic acid (PA) in calcium transport in Caco-2 cell monolayers. PA-induced calcium deficiency mice model indicated that copolymers could reverse the side effect of PA, promote calcium bioavailability, and improve gut health. Overall, these results confirmed the potentialities of DPs-COS copolymers as nutraceuticals/functional food for oral calcium delivery to promote calcium absorption and improve gut health.